Routine lung volume recruitment in boys with Duchenne muscular dystrophy: a randomised clinical trial. Issue 8 (2nd March 2022) - Katz, Sherri L; Mah, Jean K; McMillan, Hugh J; Campbell, Craig; Bijelić, Vid; Barrowman, Nick; Momoli, Franco; Blinder, Henrietta; Aaron, Shawn D; McAdam, Laura C; Nguyen, The Thanh Diem; Tarnopolsky, Mark; et al.
Abstract : Background: Impaired cough results in airway secretion retention, atelectasis and pneumonia in individuals with Duchenne muscular dystrophy (DMD). Lung volume recruitment (LVR) stacks breaths to inflate the lungs to greater volumes than spontaneous effort. LVR is recommended in DMD clinical care guidelines but is not well studied. We aimed to determine whether twice-daily LVR, compared with standard of care alone, attenuates the decline in FVC at 2 years in boys with DMD. Methods: In this multicentre, assessor-blinded, randomised controlled trial, boys with DMD, aged 6–16 years with FVC >30% predicted, were randomised to receive conventional treatment or conventional treatment plus manual LVR twice daily for 2 years. The primary outcome was FVC % predicted at 2 years, adjusted for baseline FVC % predicted, age and ambulatory status. Secondary outcomes included change in chest wall distensibility (maximal insufflation capacity minus FVC) and peak cough flow. Results: Sixty-six boys (36 in LVR group, 30 in control) were evaluated (median age (IQR): 11.5 years (9.5–13.5), median baseline FVC (IQR): 85% predicted (73–96)). Adjusted mean difference in FVC between groups at 2 years was 1.9% predicted (95% CI −6.9% to 10.7%; p=0.68) in the direction of treatment benefit. We found no differences in secondary outcomes. Conclusion: There was no difference in decline in FVC % predicted with use of twice-daily LVR for boys with DMD and relatively normal lung function. The burden associated with routine LVR may outweigh the benefit. Benefits of LVR to maintain lung health in boys with worse baseline lung function still need to be clarified. Trial registration number: NCT01999075 .